2023
DOI: 10.1111/jan.15702
|View full text |Cite
|
Sign up to set email alerts
|

Does the cultural awareness of nurses affect brain drain and xenophobia?

Abstract: AimTurkey is on the transit route of immigrants as it is located between countries where poverty and wars are intense and European countries. Therefore, there are countless immigrants from different countries in Turkey. Migrations affect every sector, especially the health sector. The aim of this study was to determine how cultural awareness of nurses, who are the cornerstone of the health system, affects brain drain and xenophobia. The problem of health care is not only on the agenda of immigrants, but also o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…In a descriptive study conducted with 257 undergraduate nursing students and 341 vocational schools of health services students to identify the relationship between intercultural effectiveness and awareness of xenophobia, the students had a high level of xenophobia (Gungor et al, 2021). The studies showed high levels of xenophobia among nurses and nursing students (Çetin & Savaş, 2023; Karadas et al, 2023). Contrary to the findings of this study, in another study conducted in Turkey with 486 nursing and midwifery students to examine the cultural sensitivity of nursing and midwifery students and its relationship with xenophobia, the students had a low level of xenophobia (Durat & Tarsuslu, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In a descriptive study conducted with 257 undergraduate nursing students and 341 vocational schools of health services students to identify the relationship between intercultural effectiveness and awareness of xenophobia, the students had a high level of xenophobia (Gungor et al, 2021). The studies showed high levels of xenophobia among nurses and nursing students (Çetin & Savaş, 2023; Karadas et al, 2023). Contrary to the findings of this study, in another study conducted in Turkey with 486 nursing and midwifery students to examine the cultural sensitivity of nursing and midwifery students and its relationship with xenophobia, the students had a low level of xenophobia (Durat & Tarsuslu, 2022).…”
Section: Discussionmentioning
confidence: 99%